World heritage forests: the world heritage convention as a mechanism for conserving tropical forest biodiversity (CIFOR and UNESCO. World Heritage Centre, 1999)
The future of the biodiversity of the world's tropical forests is intensely debated in a number of international processes. A broad consensus is emerging from these processes that the threat to forest biodiversity is one of the major environmental challenges the world faces and action is required immediately to conserve vital forest areas, especially in the tropics. The Berastagi (Indonesia) policy dialogue brought together people interested in international programmes to conserve biodiversity to discuss how the World Heritage Convention might facilitate international efforts to conserve the world's most richly biodiverse forests. The World Heritage Convention has been ratified by over 160 countries, and 33 of the world's most biodiverse forests have already been inscribed on the World Heritage List. A number of broad objectives were established, and meeting participants agreed to work through their own organisations toward these goals. A tentative list of candidate World Heritage sites was developed from which additions to the present list might be drawn. Brief papers analysing the following issues were prepared during the meeting and are included in this volume: (1) how much human modification of forests is consistent with World Heritage status, especially to dispel the myth that conservation objectives are best met by excluding people; (2) how to reconcile the interests of local people with the maintenance of the global values of the sites; and (3) how to establish scientifically defensible methods for detecting changes in the biodiversity of tropical forest sites to provide indicators for triggering adaptive management responses. The meeting concluded that the World Heritage Convention is a potentially very valuable mechanism for achieving significant medium-term targets for the conservation of forest biodiversity.